Cytoadhesion of Plasmodium falciparum-infected erythrocytes to chondroitin-4-sulfate is cooperative and shear enhanced - Rieger, Harden; Yoshikawa, Hiroshi; Quadt, Katharina; Nielsen, Morten A.; Sanchez, Cecilia P.; Salanti, Ali; Tanaka, Motomu; Lanzer, Michael (Blood, 2015)
Key Points. Cytoadhesion of parasitized erythrocytes depends on the intermolecular distance between neighboring chondroitin-4-sulfate molecules.VAR2CSA is an a
Prepublished online as Blood First Edition paper, October 28, 2014
Gesehen am 18.06.2020